Paciente de 5 años con neumonía ingresado en el área de hospitalización del Hospital General Babahoyo. - Troya Altamirano, Allinson Rolando (2020)
The present case study is based on the subject of pneumonia in a 5-year-old patient admitted to the hospitalization area of the Babahoyo general hospital, which is made up of statistical data. Several procedures and techniques covering respiratory therapy were used, such as; oxygen therapy, nebulisations, pulse oximetry, pulmonary vibrations, pulmonary palpations and respiratory physiotherapy, which were used in order to help the patient with pneumonia and thus be able to help improve their lifestyle. It was possible to detail all the processes and methods that were used by the respiratory therapist to the child in order to improve the symptomatological picture at the time of entering the emergency area and thus also obtain data from his medical history and perform a complete history and through the tests how; arterial blood tests, chest x-rays, sputum test that were prescribed by the doctor on duty to diagnose what type of pneumonia the patient presented. The result was pneumonia acquired in the community through the tests that were performed, the infection was treated by different drugs such as; antibiotics (Gentamicin, Ciprofloxacin, Amikacin) to treat pneumonia, and bronchodilators such as ipratropium bromide that was used for bronchoconstriction, improve airflow and decrease respiratory distress.